Review on swirl-type microbubble generator: Concept, technology, and applications - Drajat Indah Mawarni; Hartono Guntur Ristiyanto; Deendarlianto Deendarlianto; Wiratni Budhijanto; Mai Salem; Hakeem Niyas; Indarto Indarto (Universitas Muhammadiyah Magelang, 2023)
The Microbubble Generator (MBG) is an aeration technology capable of producing micron-sized bubbles. Several researchers have conducted previous studies and developed various types related to the microbubble generator. The swirl-type microbubble generator has demonstrated advantages over other types. It has been widely explored recently due to its simple structure, efficiency in producing micron-sized bubbles, and potential applications across various fields. Therefore, this article reviews recent developments in swirl-type bubble generator research, encompassing the definition of microbubbles, methods for generating microbubbles through experimental and numerical approaches, the performance of microbubble generators, and their applications. Based on optimized geometric parameters combined with appropriate flow conditions, the swirl-type bubble generator is predicted to produce bubbles with controlled sizes and concentrations that meet specific requirements. However, further studies are needed to delineate the fluid-gas interactions comprehensively.